A Cleavage‐Modification‐Reassembly Process Catalyzed by Rhodium and Brønsted Acid for the Synthesis of Multi‐Substituted Anilines. Issue 10 (3rd April 2020) - Liu, Xiangrong; Xiao, Guolan; Xu, Xinfang; Kang, Zhenghui; Zhang, Dan; Hu, Wenhao
Abstract: A synergistic rhodium‐ and Brønsted acid‐ catalyzed reaction of quinone imine ketals with diazo compounds to access multi‐substituted anilines is presented here. This reaction takes place through a process involving C−O bond cleavage, modification of the leaving alcoholic fragment, and selective reassembly of the reactive fragments. Moderate enantioselectivities are achieved when a chiral 1, 1'‐bi(2‐naphthol)‐based phosphoric acid is used. Abstract :